Invasion history of Harmonia axyridis (Pallas, 1773) (Coleoptera: Coccinellidae) in Ecuador - Cisneros-Heredia,Diego F.; Peñaherrera-Romero,Emilia (PeerJ, 2020)
Harmonia axyridis is a ladybird extensively used around the world for biological control of agricultural pests. However, it has become invasive in several countries, producing negative ecological and socio-economic impacts. Herein, we review the invasion history of the Harlequin Ladybird Harmonia axyridis (Pallas, 1773) in Ecuador. Although first reported in Ecuador in 2012, museum specimens date back to 2004 and it is currently established across the country, especially along the Andean region. Due to its invasive nature, further studies are urgently needed to evaluate possible impacts of H. axyridis on the Ecuadorian biodiversity and agroindustry.
Keywords: Andes; Range extension; New records; Coccinellinae; Distribution; Harlequin Ladybird; Introduced species; Elevation; Natural history